A Decision Model for Adjusting to Natural Hazard Events with Application to Urban Snow Storms - Howe, Charles W.; Cochrane, Harold C. (The Review of Economics and Statistics, 1976)
Charles W. Howe, Harold C. Cochrane, A Decision Model for Adjusting to Natural Hazard Events with Application to Urban Snow Storms, The Review of Economics and Statistics, Vol. 58, No. 1 (Feb., 1976), pp. 50-58